2021
DOI: 10.1016/j.ajps.2021.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Iron-doxorubicin prodrug loaded liposome nanogenerator programs multimodal ferroptosis for efficient cancer therapy

Abstract: Ferroptosis is a new mode of cell death, which can be induced by Fenton reaction-mediated lipid peroxidation. However, the insufficient H 2 O 2 and high GSH in tumor cells restrict the efficiency of Fenton reaction-dependent ferroptosis. Herein, a self-supplying lipid peroxide nanoreactor was developed to co-delivery of doxorubicin (DOX), iron and unsaturated lipid for efficient ferroptosis. By leveraging the coordination effect between DOX and Fe 3+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 35 publications
(72 reference statements)
0
16
0
Order By: Relevance
“…Although IP content had no significant correlation with FA saturation in BDE-153-treated roots as determined by the relationship between IP and SAFA ( R 2 = 0.4305) or USFA ( R 2 = 0.4472) (Figure C), all MBC treatments significantly inhibited UFAs in both shoots and roots as compared to BC, particularly the polyunsaturated fatty acids (PUFA) C18:2 and C18:3 (Figures A,B and S5). The uptake of Fe 2+ from IP or MBC can enhance lipid peroxidation, , and thus, decrease the UFA content in plants. More importantly, IP formation was negatively correlated with MLFA and VLFA, with R 2 values of 0.7626** and 0.9133**, respectively (Figure C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although IP content had no significant correlation with FA saturation in BDE-153-treated roots as determined by the relationship between IP and SAFA ( R 2 = 0.4305) or USFA ( R 2 = 0.4472) (Figure C), all MBC treatments significantly inhibited UFAs in both shoots and roots as compared to BC, particularly the polyunsaturated fatty acids (PUFA) C18:2 and C18:3 (Figures A,B and S5). The uptake of Fe 2+ from IP or MBC can enhance lipid peroxidation, , and thus, decrease the UFA content in plants. More importantly, IP formation was negatively correlated with MLFA and VLFA, with R 2 values of 0.7626** and 0.9133**, respectively (Figure C).…”
Section: Resultsmentioning
confidence: 99%
“…Although IP content had no significant correlation with FA saturation in BDE-153-treated roots as determined by the relationship between IP and SAFA (R 2 = 0.4305) or USFA (R 2 = 0.4472) (Figure 2C), all MBC treatments significantly inhibited UFAs in both shoots and roots as compared to BC, particularly the polyunsaturated fatty acids (PUFA) C18:2 and C18:3 (Figures 2A,B and S5). The uptake of Fe 2+ from IP or MBC can enhance lipid peroxidation, 57,58 and thus, decrease the UFA content in 3B), suggesting that IP formation could act as a barrier to prevent BDE-153 accumulation in rice roots. Pi et al also reported that IP acted as a barrier to decrease PAH and PBDE uptake by mangroves, largely by increasing PAH and PBDE accumulation on root surfaces.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…In recent decades, nanomaterials have been rapidly used in materials science and engineering applications due to their nano effects during the past decades (Forigua et al, 2021; Gu, Pan, et al, 2022; Rehan et al, 2022; Yang et al, 2021; Yuan, Fan, et al, 2023). Among these remarkable nanomaterials, nanofibers have drawn significant attention due to their diverse physiochemical properties, which could overcome the limitations of the macroscale (Yu & Huang, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of nanotechnology in medicine, nano-sized drug delivery systems (NDDS) are promising to address the above issues. [18,19] The typical nanocarriers for drug delivery include liposomes [20] , polymer micelles [21] , and metal nanoparticles [22] . Therefore, NDDS is promising for ferroptotic anticancer drug delivery.…”
Section: Introductionmentioning
confidence: 99%